2002
DOI: 10.1007/s00425-002-0837-y
|View full text |Cite
|
Sign up to set email alerts
|

Seed after-ripening and over-expression of class I β-1,3-glucanase confer maternal effects on tobacco testa rupture and dormancy release

Abstract: 'Coat-imposed' seed dormancy of many non-endospermic and endospermic species is released during after-ripening. After-ripening-mediated promotion of tobacco ( Nicotiana tabacum L.) seed germination is mainly due to a promotion of testa rupture and a similar promotion of subsequent endosperm rupture. Treatment of after-ripened or freshly harvested mature seeds with abscisic acid (ABA) delays endosperm rupture and inhibits the induction of class I beta-1,3-glucanase (betaGlu I) in the micropylar endosperm, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…The complete hydrolysis of b-glucans is facilitated by several enzymes, including endo-(1-3)-b-glucanase (Leah et al, 1995). Recent studies in tobacco seeds revealed that an up-accumulation of b-1,3 glucanase correlated with the release of seed-coat imposed dormancy during after-ripening (Leubner-Metzger, 2002, 2005. Here, Leubner-Metzger et al (2005) proposed that hydrolysis of b-glucans contributes to release the seed-coat barrier to facilitate radicle protrusion.…”
Section: An Accumulation Of Energetic Metabolism and Hydrolytic Enzymmentioning
confidence: 99%
“…The complete hydrolysis of b-glucans is facilitated by several enzymes, including endo-(1-3)-b-glucanase (Leah et al, 1995). Recent studies in tobacco seeds revealed that an up-accumulation of b-1,3 glucanase correlated with the release of seed-coat imposed dormancy during after-ripening (Leubner-Metzger, 2002, 2005. Here, Leubner-Metzger et al (2005) proposed that hydrolysis of b-glucans contributes to release the seed-coat barrier to facilitate radicle protrusion.…”
Section: An Accumulation Of Energetic Metabolism and Hydrolytic Enzymmentioning
confidence: 99%
“…Taken together, we can conclude from these results that ABA does not inhibit endosperm rupture and transition to postgermination growth by affecting TAG mobilization. Compared to freshly harvested seeds, after-ripened tobacco seeds have lower ABA contents, decreased ABA sensitivity, and enhanced bGlu I expression during imbibition (Grappin et al, 2000;LeubnerMetzger and Meins, 2000;Leubner-Metzger, 2002, 2005. ABA-sensitive expression of bGlu I in the micropylar endosperm causally contributes to endosperm rupture.…”
Section: Aba Does Not Inhibit Tobacco Seed Oil Mobilizationmentioning
confidence: 99%
“…This experimental advantage was used to study the hormonal regulation and to pinpoint the sites for class I b-1,3-glucanase (bGlu I) action (e.g. Leubner-Metzger and Meins, 2000;Leubner-Metzger, 2002, 2005. ABA inhibits the induction of bGlu I in the micropylar endosperm just before its rupture but does not affect testa rupture of tobacco.…”
mentioning
confidence: 99%
“…Anybody is familiar with the swelling of a wet grain, which breaks the outer hull and thus enables or eases the seedling's growth. But water entering the grain also starts physiological and developmental processes necessary for the early development of the embryo [1,78,194,259]. It is influenced among other parameters crucially by temperature and water supply [35,344].…”
Section: Moving Interfacesmentioning
confidence: 99%